The Zonation of Landslide Hazard at Kandangan, Temanggung, Central Java - Suratman Woro Suprojo (Universitas Muhammadiyah Surakarta, 2004)
The aim of the research are to measure the type of mass movement and landslide hazard zoning for settlement ite evaluation. Terrain unit and their characteristics are the main inputs. Terrain classification based on genetic, morphology, and lithology are important aspects in the mapping of terrain through aerial photo interpretation at scale 1 : 50.000. Sampling method is stratified random sampling. Data considered in this research consist of slope, soils, lithology, dissetion, lineament, land use, vegetation, morphometry of landslide. Laboratory analysis is done for soil physics determination. Scoring and addition method are applied in the landslide hazard zoning through GIS programme. The result of this research are that structural – denudational mountain unit shows highly landslide hazard with sil/debris slide, planar block slide as dominant processes, while in the structural – denudational hills and colluvial valley bottom and river terraces show moderately landslide hazard with soil/debris slide and soil creep as main processes and then in the peneplain and colluvial slope show low landslide hazard. The highly landslide hazard zone cover settlement at the area Krempong, Sucen, Karangseneng, Kedawung, and Margalelo.